Are Supramodality and Cross-Modal Plasticity the Yin and Yang of Brain Development? From Blindness to Rehabilitation - Cecchetti, Luca; Kupers, Ron; Ptito, Maurice; Pietrini, Pietro; Ricciardi, Emiliano (Frontiers in Systems Neuroscience, 2016)
Research in blind individuals has primarily focused for a long time on the brain plastic reorganization that occurs in early visual areas. Only more recently, scientists have developed innovative strategies to understand to what extent vision is truly a mandatory prerequisite for the brain’s fine morphological architecture to develop and function. As a whole, the studies conducted to date in sighted and congenitally blind individuals have provided ample evidence that several ‘visual’ cortical areas develop independently from visual experience and do process information content regardless of the sensory modality through which a particular stimulus is conveyed: a property named supramodality. At the same time, lack of vision leads to a structural and functional reorganization within 'visual' brain areas, a phenomenon known as cross-modal plasticity. Cross-modal recruitment of the occipital cortex in visually deprived individuals represents an adaptative compensatory mechanism that mediates processing of non-visual inputs. Supramodality and cross-modal plasticity appear to be the 'yin and yang' of brain development: supramodal is what takes place despite the lack of vision, whereas cross-modal is what happens because of lack of vision. Here we provide a critical overview of the research in this field and discuss the implications that these novel findings have for the development of educative/rehabilitation approaches and sensory substitution devices in sensory-impaired individuals.